Resistance of selected Oryza glaberrima landraces and their intra-specific breeding lines to Beninese Rice yellow mottle virus isolates - Agnoun, Y.; Yelome, I.; Sie, M.; Albar, L.; Ghesquière, A.; Silué, D. (Elsevier, 2019)
Rice yellow mottle virus (RYMV) is a widespread and damaging pathogen, endemic to Africa and affecting rice in lowland, irrigated and upland ecologies. Yield losses of 10–100% have been recorded, depending on rice genotypes, time of infection, cropping system, vector abundance and isolate pathogenicity. Control measures for this disease are based mainly on cultural practices and the use of varietal resistance. Specifically, Oryza glaberrima, the cultivated African rice species, has provided several of the known resistance alleles/genes. In this study, 160 O. glaberrima landraces, 55 of their intra-specific progenies and two controls - Tog5681 (resistant) and IR64 (susceptible) - were screened against five RYMV isolates collected from Northern Benin. Disease severity was measured on plants at 21 and 42 days after inoculation. Two cultivars - IRGC104019 and IRGC96787 (Tog5644) - from Tanzania and Nigeria respectively - and 16 intra-specific lines were identified as highly resistant to all five isolates. The genotyping of IRGC104019 and IRGC96787 revealed that they share allele rymv1-3, identified in Tog5681 (the resistant control) and that confers resistance, bringing the number of O. glaberrima accessions known to date to harbor this allele to 11. The importance of this finding and the level of resistance displayed by these two accessions strengthen the hypothesis that the African rice collection is a potential RYMV resistance donor. It is, therefore, necessary to further screen it for valorizing its usefulness in breeding programs.